Strategic Convergence: How Knowledge Sharing, Cross-Functional Collaboration, and Adaptive Leadership Drive Innovation Success - Tobari, Tobari; Dewi, Maftuhah; Naim, Sidrotun; Nur Azizah, Siti (International Journal of Business, Law, and Education, 2024)
This study investigates the relationships among knowledge sharing, cross-functional collaboration, adaptive leadership, and innovation success in organizational settings. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM), the research analyzes data collected from employees across various industries. The findings reveal that knowledge sharing significantly influences innovation success both directly and indirectly through cross-functional collaboration, which also serves as a critical mediator between adaptive leadership and innovation outcomes. Furthermore, adaptive leadership is shown to enhance cross-functional collaboration, emphasizing the importance of leadership style in fostering a collaborative culture conducive to innovation. These results underscore the necessity for organizations to cultivate knowledge-sharing practices, promote cross-functional teamwork, and develop adaptive leadership capabilities to drive innovation success. The study contributes to the literature by elucidating the dynamic interplay among these constructs and providing practical implications for managers seeking to enhance their organization's innovative capacities.